A model of paternal protection in the context of political violence: Insights from the occupied Palestinian territories. (March 2020) - Akesson, Bree; Bogossian, Aline; Gokani, Ravi
There is little research that explores how fathers protect their children in the context of political violence. Drawing upon exploratory qualitative research with 18 Palestinian families, this article proposes a model of paternal protection composed of three dimensions: (1) method of protection (how fathers protect their children), (2) focus of protection (what fathers protect their children from), and (3) locus of protection (where fathers locate the mechanisms of protection). The model contributes to a greater awareness and understanding of the daily challenges facing fathers and suggests ways that social work practice and policy can support fathers in settings of adversity.